Expression and analysis of the human cytomegalovirus UL80-encoded protease: identification of autoproteolytic sites. - Baum, E Z (1993)
The 45-kDa assembly protein of human cytomegalovirus is encoded by the C-terminal portion of the UL80 open reading frame (ORF). For herpes simplex virus, packaging of DNA is accompanied by cleavage of its assembly protein precursor at a site near its C terminus, by a protease encoded by the N-terminal region of the same ORF (F. Liu and B. Roizman, J. Virol. 65:5149-5156, 1991). By analogy with herpes simplex virus, we investigated whether a protease is contained within the N-terminal portion of the human cytomegalovirus UL80 ORF. The entire UL80 ORF was expressed in Escherichia coli, under the control of the phage T7 promoter. UL80 should encode a protein of 85 kDa. Instead, the wild-type construct produces a set of proteins with molecular masses of 50, 30, 16, 13, and 5 kDa. In contrast, when mutant UL80 is deleted of the first 14 amino acids, it produces only an 85-kDa protein. These results suggest that the UL80 polyprotein undergoes autoproteolysis. We demonstrate by deletional analysis and by N-terminal sequencing that the 30-kDa protein is the protease and that it originates from the N terminus of UL80. The UL80 polyprotein is cleaved at the following three sites: (i) at the C terminus of the assembly protein domain, (ii) between the 30- and 50-kDa proteins, and (iii) within the 30-kDa protease itself, which yields the 16- and 13-kDa proteins and may be a mechanism to inactivate the protease.